2021
DOI: 10.1101/2021.03.25.21254272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographically-targeted COVID-19 vaccination is more equitable than age-based thresholds alone

Abstract: COVID-19 mortality increases dramatically with age and is also substantially higher among Black, Indigenous, and People of Color (BIPOC) populations in the United States. These two facts introduce tradeoffs because BIPOC populations are younger than white populations. In analyses of California and Minnesota--demographically divergent states--we show that COVID vaccination schedules based solely on age benefit the older white populations at the expense of younger BIPOC populations with higher risk of death from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…Because racial and ethnic minorities are overrepresented among essential workers ( Blau et al, 2020 ; Chang et al, 2021 ; Kissler et al, 2020 ), further modeling studies could evaluate the impact of such strategies on also reducing inequities in COVID-19 infection rates. Wrigley-Field et al took a different methodological approach, projecting demographically stratified death rates from 2020 into 2021 assuming various vaccination strategies ( Wrigley-Field et al, 2021 ). In line with the prior study, they found that vaccination strategies that prioritized geographic areas based on socioeconomic criteria or prior COVID mortality rates outperformed age-based strategies in reducing overall mortality and inequities in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Because racial and ethnic minorities are overrepresented among essential workers ( Blau et al, 2020 ; Chang et al, 2021 ; Kissler et al, 2020 ), further modeling studies could evaluate the impact of such strategies on also reducing inequities in COVID-19 infection rates. Wrigley-Field et al took a different methodological approach, projecting demographically stratified death rates from 2020 into 2021 assuming various vaccination strategies ( Wrigley-Field et al, 2021 ). In line with the prior study, they found that vaccination strategies that prioritized geographic areas based on socioeconomic criteria or prior COVID mortality rates outperformed age-based strategies in reducing overall mortality and inequities in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…the combination of geography (hence, social determinants) and age when considering vaccination priorities to allow for the joint probability of acquisition risk and severity risk when allocating limited vaccination supply in the short-term. (51) Such efforts would also need to include active, community-tailored efforts to address vaccine confidence/trust which may be lower in communities most affected by COVID-19;(52) and account for implementation challenges with neighbourhood-specific vaccine delivery ensuring it is equitable. (53, 54) Second, the occupational and housing risks identified here may be overcome with structural interventions such as paid leave, housing supports, and alleviating barriers to testing and healthcare access.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, geographic targeting of vaccine doses to disadvantaged communities has potential to accelerate progress toward a more equitable convergence of coverage by July. Previous studies have suggested that disadvantage indices should be used to prioritize allocation (5,6). Beyond their role in improving the equity of the nation's vaccination campaign, place-based allocation strategies are also likely more effective overall, since individuals living in disadvantaged areas, predominantly low-income individuals and people of color, have borne a disproportionate burden of COVID-19 cases, hospitalizations, and deaths (7).…”
Section: Discussionmentioning
confidence: 99%